Economic terms in the news during the Great Recession: A diachronic sentiment and collocational analysis. - Fernández-Cruz, Javier; Moreno-Ortiz, Antonio Jesús (Peter Lang, 2024)
This book explores the evolution of sentiment in economic terms in the press during financial crises applying a combination of sentiment analysis techniques and usage fluctuation analysis on a diachronic corpus derived from editorials in quality newspapers during the Great Recession. The book uncovers two key findings: first, certain economic terms become event words during times of crisis due to their increase use in the press and the general public, revealing rapid semantic changes in economic terms caused by major socio-economic events. Second, sentiment-laden collocations are found to be influenced by culture, highlighting language’s adaptability to financial upheavals. This work proposes an innovative methodology that combines lexicon-based Sentiment Analy sis, Corpus Linguistics, and qualitative Dis course Analysis to shed light on how language shapes economic discourse, making it a valuable resource for scholars exploring the relationship between language and historic events. Javier Fernández-Cruz is a lecturer at the University of Málaga and a member of the Tecnolengua Research Group. He has worked at universities in France, Italy and Ecuador. With a dedicated focus on digital humanities, his research efforts concentrate on corpus linguistics, sentiment analysis and specialized languages. Antonio Moreno Ortiz is an associate professor at the University of Malaga. His research focuses on computational and corpus linguistics, including the development of software and resources. He leads the Tecnolengua Research Group, which focuses on computer-mediated communication, with special emphasis on sentiment analysis and social media.
https://www.peterlang.com/repository-policy/
Keywords: Análisis del discurso; Lingüística; Corpus linguistics; Linguistica de corpus; Lenguaje económico; Análisis de sentimiento; Análisis de sentimientos; Sentiment analysis; Press; Crisis; Great recession; Gran recesión; Lenguaje periodístico; Procesamiento del lenguaje natural; Discourse analysis; The Guardian; The New York Times; Diachronic change; Cambio semántico; Terminology; Terminología; Extracción de terminología; Collocations